Association of antithrombin-III and platelet count with pregnancy induced hypertension - Sarkar, Purnima Dey; Sogani, Sonal (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Preeclampsia is referred to as the “disease of the theories” because of the multiple hypotheses proposed to explain its occurrence. Despite considerable research, the causes of preeclampsia remain unclear. It is multifactorial in nature and recent research has focused on the measurements of various prothrombotic markers for detection of latent clotting pathway activation. This study was undertaken to determine the changes in the levels of plasma Antithrombin -III (AT-III) and platelet count in preeclamptic women and its comparison with healthy non-pregnant women and normal pregnant womenand its correlation with severity of disease in order to evaluate if it can be used as a marker for severity of pregnancy induced hypertension (PIH). This is the case-control hospital based study carried in the Department of Biochemistry M.G.M. Medical College and associated M.Y. Hospital. Indore (M.P.). 40 women with preeclampsia in the third trimester of pregnancy constituted the study group. The study group was further divided into two subgroups as mild and severe preeclampsia. Age and gestational age matched 23 healthy non –pregnant and 28 normal pregnant women were taken as a control group. There were no significant differences among the three groups in age and body mass index (BMI) but significantly higher differences in gestational age, systolic and diastolic blood pressure was observed. When compared with control groups (healthy non-pregnant and normal pregnant women), the levels of AT-III in preeclamptic group was significantly lower. Although there was no significant difference in the levels of AT-III between healthy non-pregnant and normal pregnant women. The platelet count between healthy non-pregnant and normal pregnant women showed statistically significant difference whereas statistically higher significant difference was observed when comparison was done between healthy non-pregnant women and preeclamptic women and normal pregnant women and preeclamptic women. It was concluded from the study that the reduction of platelet count and AT-III are the main predictors to predict and monitor the severity of the condition.